Melodi dalam Gambar - Fornia, S.I.Kom, M.I.Kom, Fornia, S.I.Kom, M.I.Kom (Akademi Komunikasi SAE Indonesia, 2024)
This research addresses several important aspects of the use of music in film, including how music can convey emotions, increase tension and anticipation, aid memory and film recognition, and reinforce emotional points. In addition, this study also discusses how music can strengthen emotional points. The study used data analysis from both film content analysis to determine the use of music in various narrative contexts and analyzed the relationship between the type of music used in the film, the atmosphere created, and the emotional response of the audience. The results discuss the important role of music in films in influencing the emotions of the audience and deepening their experience in understanding visual stories. The study also reviewed various aspects, including the emotional influence of music, increased tension and anticipation, assistance in memory and film recognition, reinforcement of emotional points, requirements for music to be effective, influence on character identification and narrative consistency, as well as music composition techniques and sound effects that affect the atmosphere of the film.